Experimental and numerical investigations of aerospace alloys: Effect of machining - Peddaiah P.C.; Dodla S. (My University, 2025)
Aerospace materials like Ti6Al4V and Inconel 718 have exceptional abilities such as high strength, good corrosion resistance, and low specific weight. These properties make them difficult to machine due to rapid tool wear, high cutting forces, and heat generation. Microstructural characterization has been performed for these alloys to identify the phases and precipitates. With the help of machining simulations, experimental trial and error can be avoided. Numerical simulations predict the behavior of materials like Ti6Al4V and Inconel 718 under various machining conditions. They provide insights into stress distribution, temperature rise, and chip formation, which are crucial for understanding how these materials respond to machining. By simulating different cutting parameters (e.g. speed, feed rate, and depth of cut), optimal conditions can be identified to minimize tool wear, improve surface finish, and reduce machining time. Achieving a high-quality surface finish is challenging with these materials. Simulations can predict the impact of different machining parameters on surface integrity, allowing for adjustments before actual machining. Three-dimensional finite element-based machining simulations are performed using the ABAQUS. The current work includes Johnson-Cook damage model parameters included in the simulation with the aid of the program ABAQUS/EXPLICIT. The numerous sets of tests carried out are also stated, along with the workpiece and tool-optimized geometry. The outcomes for cutting forces about time for Ti6Al4V and Inconel 718 are retrieved. The arbitrary Lagrangian–Eulerian approach has been used for these simulations. A coupled thermo-mechanical study is conducted on different sets of materials under various machining conditions. In addition, ultrasonic-assisted cutting on aerospace materials is also being studied, along with a comparison of the cutting forces used by conventional cutting. On the surfaces of aerospace materials that have been machined, temperature and von Mises stress distribution are discussed for both ultrasonic-assisted cutting and conventional cutting. The reaction forces generated for titanium alloy Ti6Al4V under conventional cutting are cutting force (RF3), and the thrust force (RF2) were 56 and 14 N, respectively. For the Inconel 718, the cutting and thrust forces are 75 and 27 N, respectively. The maximum temperature and stress under conventional cutting attained in Ti6Al4V are 670 K and 1.74 GPa, respectively. For the Inconel 718, the maximum temperature and stress under conventional cutting are 596 K and 1.65 GPa. There is a reduction in the forces, maximum temperature, and stress for the ultrasonic-assisted cutting. © IMechE 2024.